Method for producing three-dimensional porous adsorbent structure
By constructing and processing the construction materials containing inorganic porous adsorbent materials and organic binder materials, the problems of high energy consumption, complex process steps and low accessibility of adsorbents in the production process of the three-dimensional porous adsorbent structure in the prior art are solved, and efficient and low-cost three-dimensional porous adsorbent structure production are achieved.
Patent Information
- Application Number
- CN202380060419.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-08
- Filing Date
- 2023-09-08
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art has problems such as high energy consumption, complex process steps and low accessibility of adsorbents when producing three-dimensional porous adsorbent structures, resulting in low efficiency and increased costs.
By constructing a construction material containing an inorganic porous adsorbent material and an organic binder material, 3D porous green body is deposited in a layered manner, and phase conversion is performed by exposure to the non-solvent of the organic binder material, and finally drying is obtained.
This method reduces energy consumption, simplifies process steps, improves accessibility of adsorbents, maintains the micropore volume and activity of the initial adsorbent material, and saves time, complexity and cost.
Smart Images

Figure CN119730952A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing a three-dimensional porous adsorbent structure. The present invention further relates to a three-dimensional porous adsorbent structure, such as obtained by the method of the present invention. Background Art
[0002] Gas separation and purification, as well as catalysis, have become an integral part of the chemical and petrochemical industries. As a result, extensive research is being conducted to improve the efficiency and sustainability of currently available technologies, and the development of new materials that can meet these demanding specifications is ongoing.
[0003] The development of porous materials that can specifically interact with the environment (either liquid or gas streams) has received increasing attention because these materials can be used in a range of applications. Gas or liquid purification and separation methods based on the adsorption of specific compounds require a packing or monolithic design of adsorbent particles to allow the interaction of the gas or liquid stream with the adsorbent particles. In addition, heterogeneous catalysis in the gas or liquid phase is based on the interaction of the feed with the packing material.
[0004] The most common geometries currently used for gas separation and catalytic applications include pellets, extrudates, and granules because of their simple and economically feasible manufacturing processes. However, packed beds of this type of shape present several disadvantages, such as large pressure drops when used in reactor columns and limited mass transfer due to slow diffusion to the particle core (which results in inefficient utilization of the catalyst or adsorbent material).
[0005] It has been found that porous monoliths offer a promising alternative, as they allow for lower pressure drops and limit the reduction of mass transfer to the ordered packing and open channelling of the structure.
[0006] One method for producing monolithic catalyst structures is by coating a porous inert monolithic support. However, coating an inert support generally results in limited catalyst or adsorbent loading. In addition, the surface adhesion of the coating may be limited, with the risk of leaching of valuable materials. This makes such products less useful and less efficient.
[0007] Another method for producing porous adsorbent structures or monolithic catalyst structures is from a suspension or paste in a layered manner, for example by stacking a plurality of layers. There are different methods for making products in a layered manner, one of which is additive manufacturing or 3D printing.
[0008] 3D printing has become a technology of interest for many applications, as it allows the production of specific designs and products that cannot be produced in other ways. 3D printed structures can be used in a large number of applications, such as in filtration, separation, catalysts, construction, etc. Different 3D printing methods are known today, and 3D printed products with a wide range of possible compositions and properties can be produced. In addition, the design of 3D printed structures may vary widely in recent times.
[0009] Particular 3D printing techniques for producing 3D printed articles in a layered manner from a building material (usually a paste or (viscous) suspension) involve (micro)extrusion of the paste or suspension layer by layer in the form of filaments, fibers or strands. Such techniques are known as robocasting, microextrusion or Direct Ink Writing (DIW). Typical building materials used in these techniques include an active compound, a binder material and a solvent.
[0010] 3D printing of inorganic materials has been performed by using a building material, which is a combination of a (typically inorganic) active compound and one or more organic and / or inorganic binders to ensure the required mechanical strength of the 3D printed structure. Examples of inorganic active compounds are ceramic materials, inorganic oxides and mineral materials, such as various types of clays, zeolites, silica or alumina. However, such 3D printed inorganic structures are generally too brittle. Further, they typically require several post-processing steps, including heat treatment (calcination) and / or sintering of the 3D printed structure. Since the heat treatment causes the decomposition of the organic binder, the carbon residues of such decomposition may remain in the structure and block parts of the porous structure or inactivate the active compound. In addition, the heat treatment is generally time-consuming and / or energy-consuming.
[0011] A promising alternative is to incorporate inorganic materials into organic matrices to develop hybrid composites.
[0012] 'Robocasting of porous alumina hollow fibre monoliths by non-solventinduced phase inversion', Michielsen, B., Mertens, M. et al., Open Ceramics 6, (2021) discloses 3D printed porous hollow alumina (Al 2 O 3 ) filaments. The 3D structure is formed by extruding (automatic slip casting) a porous Al 2 O 3The method is constructed by mixing a paste of Amperit powder, polyetherimide as a polymer binder, and N-methyl-2-pyrrolidone as a solvent. The humid atmosphere induces phase inversion, providing sufficient strength for the extruded hollow fiber to be self-supporting. The extruded filaments, such as in the shape of a 3D structure, are then immersed in a non-solvent to complete the phase inversion, thereby fully solidifying the filaments. The solidified green body is then dried, calcined and sintered to obtain an alumina hollow fiber structure. Calcination removes the polymer binder and organic additives, and the porous Al2O3 is obtained using the provided sintering. 2 O 3 Final properties of the fiber.
[0013] WO 2009 / 027525 discloses a method for producing a three-dimensional microporous filament structure. The structure is obtained by 3D printing a suspension containing inorganic material (particularly titanium) particles, a solvent and one or more (organic) binders into a green body based on a filament, and then phase conversion is carried out by a non-solvent to solidify the filament. The solidified green body is then dried, calcined and sintered. Calcination under an inert atmosphere causes pyrolysis of organic materials to produce carbonaceous pyrolysis products. These carbonaceous products formed in this way may be adsorbed in a porous structure and may reduce or block the accessibility of the active sites of the structure. In addition, sintering causes the pores in the solidified green body to shrink, that is, sintering densifies the solidified green body and causes the specific surface of the final three-dimensional porous structure to decrease. Further, sintering may cause the loss of functional groups and may cause the embrittlement of inorganic materials, particularly titanium.
[0014] 'Development of 3D-printed polymer-zeolite composite monoliths for gas separation', Thakkar, H., Lawson, S. et al., Chemical Engineering Journal, 348, pp. 109-116 (2018) discloses the development of a 3D porous adsorbent structure comprising about 30 wt.% zeolite 13X or 5A embedded in about 40 wt.% Torlon (polyamide-imide polymer) binder, further comprising additives, for removal of CO from flue gases 2 Such monoliths are obtained by extruding a paste containing Torlon, zeolite, a polymer binder (polyvinyl pyrrolidone) and N-methyl-2-pyrrolidone (NMP) and water as solvents. After extruding a single layer of the structure, DI water is poured dropwise on the last extruded layer to induce a phase inversion of that layer. This provides the partially completed structure (and the final structure) with self-supporting properties.
[0015] One of the disadvantages of the above methods is that a humid environment is required during extrusion or repeated extrusion-phase inversion cycles to ensure that the porous structure (i.e., green body) is self-supporting during extrusion. In other words, complex and expensive measures are required to avoid collapse or deformation of the 3D monolith during the building step. This makes the process time-consuming, complex and expensive.
[0016] Another disadvantage of the above method is that the obtained three-dimensional porous adsorbent structure shows a significantly reduced specific surface area of the active material (e.g., zeolitic material) compared to the initial surface area of the active material before its incorporation into the building material or paste composition. In other words, the accessibility of the active material in the three-dimensional porous structure is greatly reduced. Yet another disadvantage is that the micropore volume is significantly reduced when compared to the micropore volume of the initial active material (i.e., before its incorporation into the building material or paste composition). In addition, the amount of active material incorporated into the three-dimensional porous adsorbent structure is low, which results in an adsorbent structure with a low adsorbent capacity.
[0017] 'Chemically active, porous 3D-printed thermoplastic composites', Evans KA., Kennedy ZC et al., ACS Applied Materials & Interfaces, 10, pp. 15112-15121 (2018) discloses the production of three-dimensional metal organic framework (MOF)-thermoplastic polymer composites with complex internal structural features via a standard 3D printer. Polylactic acid (PLA) pellets as a thermoplastic polymer are dissolved in chloroform. The zeolite imidazolate framework ZIF-8 as a MOF is dispersed in ethyl acetate, and the PLA solution is subsequently added to the ZIF-8 dispersion. The resulting mixture is then formed into a film by casting, heating and drying, thereby removing most of the solvent. The film is then formed into filaments by extrusion. The filaments are then printed by 3D printing.
[0018] US2022 / 0250029 discloses a method for producing a 3D printed zeolite monolith comprising a zeolite material and a binder. The monolith is prepared by mixing the zeolite and the binder, followed by adding distilled water to obtain a paste. The paste is extruded in an automatic slip casting 3D printer, then dried at room temperature to partially remove the water, and then heated in an oven to remove the remaining water and allow high strength to be established and to avoid surface cracking. Sintering may then be performed to decompose and remove the binder and enhance the mechanical strength of the monolith. Summary of the invention
[0019] The present invention aims to overcome one or more of the above disadvantages. It is an object of the present invention to provide a three-dimensional (3D) porous adsorbent structure or adsorbent article and a method for producing the 3D porous adsorbent structure or adsorbent article, which has reduced energy consumption and requires a reduced number of process steps to obtain the 3D porous adsorbent structure, thereby saving time, complexity and cost. The object is to provide a method that allows the production of a 3D porous adsorbent structure with high adsorbent accessibility, wherein access to the adsorbent material (pores) in the adsorbent structure is largely maintained compared to the initial or original adsorbent material, and thus the activity of the adsorbent is largely maintained or retained. The object is also to provide a method for producing a 3D porous adsorbent structure, wherein most of the structure of the adsorbent material is preserved.
[0020] According to a first aspect of the present invention, there is therefore provided a method for producing a 3D porous adsorbent structure as set out in the accompanying claims. The method for producing a three-dimensional porous adsorbent structure as described herein comprises the steps of constructing a 3D porous green body, inducing a phase inversion of the 3D porous green body, and drying the porous green body, thereby obtaining the three-dimensional porous adsorbent structure.
[0021] The porous green body is obtained in a layered manner from a building material comprising an inorganic porous adsorbent material and an organic binder material. At least a portion of the organic binder material is dissolved in a solvent. In other words, the building material also comprises a solvent. Advantageously, at least 10% by weight, such as at least 25% by weight, preferably at least 50% by weight, for example at least 60% by weight, at least 70% by weight, at least 80% by weight, more preferably at least 90% by weight, for example at least 95% by weight, or 100% by weight of the organic binder material, based on the total weight of the organic binder material, is dissolved in the solvent.
[0022] The term "build material" is used in the present disclosure for compositions that are used to produce or manufacture three-dimensional porous adsorbent structures. In particular, the build materials of the present disclosure are built into 3D porous green bodies, which are then converted into 3D porous adsorbent structures. Synonyms of "build material" as used in the present disclosure include "building material" and "3D printing composition", the latter of which is used when the porous green body is obtained by a 3D printing process.
[0023] The porous green body is obtained in a layered manner by depositing the building material in a plurality of stacked layers. Advantageously, at least some of the filaments within at least one of the plurality of layers are spaced apart from each other, for example deposited at a distance from each other.
[0024] The present invention therefore relates to a method for producing a three-dimensional porous adsorbent structure, the method comprising:
[0025] constructing a three-dimensional (3D) porous green body from a building material comprising an inorganic porous adsorbent material and an organic binder material, wherein at least a portion of the organic binder material is dissolved in a solvent, wherein the building material is deposited as filaments in a plurality of stacked layers to obtain the three-dimensional porous green body, wherein at least some of the filaments within at least one of the plurality of layers are spaced apart from each other,
[0026] Inducing a phase inversion of the three-dimensional porous green body by exposing the three-dimensional porous green body to a non-solvent for the organic binder material, thereby obtaining a solidified three-dimensional porous green body, and
[0027] drying the solidified three-dimensional porous green body to obtain the three-dimensional porous adsorbent structure,
[0028] wherein the build material comprises between 30% and 70% by weight of the inorganic porous adsorbent material and between 5% and 30% by weight of the organic binder material based on the total weight of the build material, wherein the organic binder material is at least partially retained in the three-dimensional porous adsorbent structure, and wherein the three-dimensional porous adsorbent structure has an adsorbent accessibility of at least 40%, wherein the adsorbent accessibility is calculated according to formula (I)
[0029]
[0030] in
[0031] S BET,结构 is the BET surface area of the three-dimensional porous adsorbent structure,
[0032] S BET,吸附剂 is the BET surface area of the initial inorganic porous adsorbent material,
[0033] X is the weight percentage of the inorganic porous adsorbent material based on the total weight of the three-dimensional porous adsorbent structure,
[0034] And wherein the BET surface area of the initial inorganic porous adsorbent material and the three-dimensional porous adsorbent structure is determined from an argon adsorption isotherm at 87K.
[0035] Advantageously, the three-dimensional green body is constructed by 3D printing technology. In other words, the 3D porous adsorbent structure is advantageously a porous 3D printed adsorbent structure. The 3D porous green body can be obtained by any 3D printing technology that allows to obtain a 3D porous structure in a layered manner. Examples of suitable 3D printing technologies include micro-extrusion of building materials (e.g., viscous pastes or solutions) (also known as automated slip casting or direct ink writing (DIW)), fused filament fabrication (FFF; also known as extrusion of molten polymer material through a nozzle or orifice), and binder jetting.
[0036] Advantageously, the inorganic porous adsorbent material comprises one or more of the following: zeolite adsorbent material, metal organic framework (MOF) adsorbent material, metal oxide, carbon-based material, clay, molecular sieve, resin and MXene (i.e., a few atoms thick layer of transition metal carbide, nitride or carbonitride). The term "a few atoms thick layer" is used in the present disclosure for a layer with a thickness between 1 and 20 atoms, preferably between 1 and 10 atoms.
[0037] The inorganic porous adsorbent material may further comprise a catalytically active material. Advantageously, the catalytically active material is active at the temperatures to which the porous green body and the three-dimensional porous adsorbent structure are exposed during production and use. Advantageously, the catalytically active material is active at a temperature below the maximum continuous use temperature of the organic binder material (as defined by the Underwriter Laboratory (UL 746B) Relative Thermal Index (RTI)), and preferably at a temperature below 180°C.
[0038] The catalytically active material is advantageously provided on the surface of the inorganic porous adsorbent material. Advantageously, the catalytically active material is fixed (such as adsorbed) on the surface of the inorganic porous adsorbent material. The catalytically active material may be provided on the surface of the inorganic porous adsorbent material before the inorganic porous adsorbent material is added to the build paste. Alternatively or additionally, the catalytically active material may be provided on the surface of the inorganic porous adsorbent material after the 3D porous adsorbent structure has been obtained.
[0039] Advantageously, the catalytically active material comprises one or more of an enzyme and a microorganism (such as yeast or bacteria) or is substantially composed of it. In other words, the catalytically active material is advantageously a biocatalytically active material, i.e., for use in biocatalysis. The limiting examples of enzymes include amylases such as starch, glucose, fructose and dextrose, lipases, ketoreductases, halogenases, methyltransferases and aldolases.
[0040] The building material comprises at least 30% by weight, preferably between 30 and 70% by weight, such as between 40 and 60% by weight, more preferably between 45 and 55% by weight of the inorganic porous adsorbent material based on the total weight of the building material.
[0041] This organic binder material advantageously comprises phase inversion polymer or is substantially composed of it. Advantageously, this organic binder (this phase inversion polymer) material advantageously comprises one or more of the following: polysulfone, polyethersulfone, cellulose acetate, polyvinylidene fluoride, polyacrylonitrile, polyethylene-to-vinyl alcohol, polycarbonate, polyimide, polyetherimide, polyamide or polyamide-imide.
[0042] The build material comprises 30% or less by weight, preferably between 5 and 30% by weight, such as between 5 and 20% by weight, more preferably between 10 and 15% by weight of the organic binder material based on the total weight of the build material.
[0043] The solvent advantageously comprises a polar aprotic solvent. Advantageously, at least a portion of the organic binder material is dissolved in the solvent. Advantageously, the phase inversion polymer is dissolved in the solvent in the construction material. Advantageously, the solvent advantageously comprises the following or is substantially composed of: N-methyl-pyrrolidone (NMP), acetone, dimethyl-acetamide (DMAc), dimethylformamide (DMF), dimethyl sulfoxide (DMSO), tetrahydrofuran (THF), dioxane, acetic acid, formyl piperidine, morpholine, s-caprolactam, gamma-butyrolactone, methyl ethyl ketone, chloroform or a combination of two or more thereof. Advantageously, the construction material comprises a solvent between 5% and 65%, preferably between 20% and 55%, by weight based on the gross weight of the construction material.
[0044] The phase transformation of the three-dimensional porous green body is induced by exposing it to a non-solvent for the organic binder material, thereby inducing the solution to separate into a binder-rich phase and a binder-poor phase. After further separation, the solubility of the binder in the solvent decreases, and a solid phase with a specific morphology will be formed, thereby obtaining a solidified 3D porous green body.
[0045] Advantageously, the non-solvent comprises or consists essentially of a polar protic solvent such as water, an alcohol, an acid, or a combination thereof.
[0046] Advantageously, the phase inversion is induced by exposing the three-dimensional porous green body to a non-solvent for the phase inversion polymer.
[0047] Advantageously, the phase inversion is induced by immersing the three-dimensional porous green body in the non-solvent and / or by atomizing the non-solvent onto the three-dimensional porous green body.
[0048] Advantageously, the solidified three-dimensional porous green body obtained after the phase inversion of the three-dimensional porous green body is dried at a temperature lower than the maximum continuous use temperature of the organic binder material. As used herein, the term "maximum continuous use temperature" refers to the highest acceptable temperature, above which the mechanical or electrical properties of a part made of a material (here, an organic binder material) significantly deteriorate within the reasonable life of the product (here, a 3D porous adsorbent structure). The maximum continuous use temperature may be defined by the Underwriters Laboratory (UL 746B) Relative Thermal Index (RTI).
[0049] Advantageously, the solidified three-dimensional porous green body obtained after phase inversion of the three-dimensional porous green body is dried at a temperature between 20°C and 180°C, preferably between 20°C and 150°C, such as between 20°C and 130°C.
[0050] Advantageously, the three-dimensional porous green body and the three-dimensional porous adsorbent structure are not exposed to a temperature above the maximum continuous use temperature of the organic binder material, wherein the maximum continuous use temperature is as defined hereinbefore. Advantageously, any heat treatment to which the three-dimensional porous green body and the three-dimensional porous adsorbent structure are subjected is carried out at a maximum temperature of 180° C. Thus, and advantageously, the three-dimensional porous adsorbent structure is not subjected to any of the calcination and sintering operations, as calcination and sintering are typically carried out at temperatures above at least 200° C., and more often above 300° C.
[0051] The three-dimensional porous adsorbent structure obtained after drying comprises at least a portion of the organic binder material contained in the building material. In other words, the organic binder material at least partially remains in the three-dimensional porous adsorbent structure.
[0052] The 3D porous adsorbent structure obtained by the method of the present disclosure has an adsorbent accessibility of at least 40%, such as at least 50% or at least 60%. The adsorbent accessibility is advantageously calculated according to formula (I):
[0053]
[0054] in
[0055] S BET,结构 is the BET surface area of the three-dimensional porous adsorbent structure,
[0056] S BET,吸附剂 is the BET surface area of the initial (or pristine) inorganic porous adsorbent material,
[0057] X is the weight percentage of the inorganic porous adsorbent material based on the total weight of the three-dimensional porous adsorbent structure,
[0058] And wherein the BET surface area is determined by the argon adsorption isotherm of the initial inorganic porous adsorbent material and the three-dimensional porous adsorbent structure at 87K.
[0059] "Initial porous adsorbent material" means according to the present invention the inorganic porous adsorbent material before being incorporated into a building material (ie the original porous adsorbent material).
[0060] According to a second aspect of the present invention there is provided a three-dimensional porous adsorbent structure as set out in the accompanying claims. Advantageously, the structure is obtainable by the method of the first aspect.
[0061] The three-dimensional porous adsorbent structure as described herein comprises filaments in a plurality of stacked layers. At least some of the filaments in a same layer of the plurality of layers are spaced apart from each other.
[0062] The three-dimensional porous adsorbent structure as described herein comprises at least 50% by weight, preferably between 70% and 98% by weight, more preferably between 80% and 95% by weight of an inorganic porous adsorbent material based on the total weight of the three-dimensional porous adsorbent structure. Advantageously, the inorganic porous adsorbent material is as described above.
[0063] The three-dimensional porous adsorbent structure as described herein comprises 50% by weight or less, preferably between 2% and 30% by weight, more preferably between 5% and 20% by weight of an organic binder material based on the total weight of the three-dimensional porous adsorbent structure. Advantageously, the organic binder material is as described above. In particular, the organic binder material advantageously comprises or consists essentially of a phase inversion polymer.
[0064] Advantageously, the three-dimensional porous adsorbent structure has an adsorbent accessibility of at least 40%, such as at least 50% or at least 60%. Advantageously, the adsorbent accessibility is calculated according to formula (I) as described hereinbefore.
[0065] Advantageously, the three-dimensional porous adsorbent structure has a micropore volume of at least 30% of the micropore volume of the initial (or original) inorganic porous adsorbent material, wherein "micropore volume" means the total volume of micropores in the structure. The micropore volume is advantageously and preferably determined by the t-plot method based on the argon adsorption isotherms at 87K of the initial inorganic porous adsorbent material and the three-dimensional porous adsorbent structure.
[0066] Another aspect of the invention relates to the use of the 3D porous adsorbent structure of the second aspect for gas adsorption and / or liquid adsorption applications. Advantageously, gas adsorption and liquid adsorption include separation of one or more compounds or components from a gas stream or a liquid stream, respectively, and / or purification of a gas stream or a liquid stream, respectively. Advantageously, adsorption, advantageously gas adsorption includes CO 2 , H 2 O, volatile organic compounds (VOC), sulfur oxides (SO x ) and nitrogen oxides (NO x ) is adsorbed by one or more of the following.
[0067] Advantageously, the three-dimensional porous adsorbent structure is not exposed to temperatures above the maximum continuous use temperature of the organic binder material during its use, as defined by the Underwriters Laboratory (UL 746B) Relative Thermal Index (RTI). Advantageously, the three-dimensional porous adsorbent structure is not exposed to temperatures above 180° C. during its use.
[0068] Advantages of the methods of the present invention include the ability to produce mechanically strong 3D porous adsorbent structures that include or maintain a large accessibility of the adsorbent material provided in the adsorbent structure. Further, these methods allow to maintain the micropore volume of the initial inorganic porous adsorbent material to a large extent, i.e. the method does not significantly fill or cover the (micro)pores of the inorganic adsorbent material.
[0069] Furthermore, the method of the present invention is suitable for producing 3D porous adsorbent materials and structures that are low temperature stable or sensitive to oxidation or thermal decomposition. BRIEF DESCRIPTION OF THE DRAWINGS
[0070] Aspects of the present invention will now be described in more detail with reference to the accompanying drawings, in which like reference numerals indicate like features, and in which:
[0071] Figure 1 The argon adsorption isotherms of three 3D porous adsorbent structures obtained by the method of the present invention at 87K are shown.
[0072] Figure 2 The pore size distributions of three 3D porous adsorbent structures obtained by the method of the present invention are shown.
[0073] Figure 3A and 3B Scanning electron microscopy (SEM) images showing the surface and cross section, respectively, of a first 3D porous adsorbent structure obtained by the method of the present invention, measured on a single extruded fiber.
[0074] Figure 4A and 4BScanning electron microscopy (SEM) images showing the surface and cross section, respectively, of a second 3D porous adsorbent structure obtained by the method of the present invention, measured on a single extruded fiber.
[0075] Figure 5A and 5B Scanning electron microscopy (SEM) images showing the surface and cross section, respectively, of a third 3D porous adsorbent structure obtained by the method of the present invention, measured on a single extruded fiber.
[0076] Figure 6 The pore size distributions of mesopores and macropores of three 3D porous adsorbent structures obtained by the method of the present invention are shown.
[0077] Figure 7 It represents the cumulative pore volume of mesopores and macropores of the three 3D porous adsorbent structures obtained by the method of the present invention.
[0078] Figure 8 represents the CO as a function of pressure for the reference 3D porous adsorbent structure 2 Adsorption capacity.
[0079] Fig. 9 represents the CO as a function of pressure of the first 3D porous adsorbent structure obtained by the method of the present invention 2 Adsorption capacity.
[0080] Fig.10 : represents the CO as a function of pressure of the second 3D porous adsorbent structure obtained by the method of the present invention 2 Adsorption capacity.
[0081] Fig.11 : represents the CO as a function of pressure of the third 3D porous adsorbent structure obtained by the method of the present invention 2 Adsorption capacity.
[0082] Fig.12 Shown is the water adsorption capacity of the reference 3D porous adsorbent structure as a function of pressure.
[0083] Fig.13 . The water adsorption capacity of the first 3D porous adsorbent structure obtained by the method of the present invention as a function of pressure is represented.
[0084] Fig.14 Graph showing the water adsorption capacity of the second 3D porous adsorbent structure obtained by the method of the present invention as a function of pressure.
[0085] Fig.15 Graph showing the water adsorption capacity of the third 3D porous adsorbent structure obtained by the method of the present invention as a function of pressure.
[0086] Fig.16 Water uptake for a humidity step from 5% RH to 10% RH as a function of time is shown for a reference 3D porous adsorbent structure and three 3D porous adsorbent structures obtained by the method of the present invention.
[0087] Fig.17 Water uptake for a humidity step from 5% RH to 10% RH as a function of time is shown for a reference 3D porous adsorbent structure and three 3D porous adsorbent structures obtained by the method of the present invention.
[0088] Fig.18 10% partial pressure of CO at a relative time up to 1250 seconds for the reference 3D porous adsorbent structure and the three 3D porous adsorbent structures obtained by the method of the present invention 2 Penetration curve. DETAILED DESCRIPTION
[0089] In the first step of the method according to the present disclosure, a 3D porous green body is constructed in a layered manner from a building material. The building material refers to a viscous paste, emulsion or solution. The building material comprises an inorganic porous adsorbent material and an organic binder material at least partially, and preferably completely, dissolved in a solvent. In other words, the building material comprises a solvent, an inorganic porous adsorbent material and an organic binder material.
[0090] Advantageously, the method does not include removing at least a portion of the solvent from the build material prior to building the 3D porous green body.
[0091] Porous green compacts can be obtained by any layered manufacturing technology that allows porous structures to be obtained. Particularly suitable technology is (micro) extrusion, which includes extruding the building material in the form of filaments or strands through a nozzle or orifice. Advantageously, the nozzle or orifice has a diameter between 20 μm and 5 mm, preferably between 30 μm and 4 mm, more preferably between 50 μm and 3 mm, for example, between 100 μm and 2 mm. Advantageously, strands or filaments are deposited layered on the printing surface, thereby producing a green compact constructed as a plurality of stacked layers. Nozzles or printing surfaces are arranged on a positioning stage (such as an XY-stage) to extrude filaments or strands in a predetermined pattern. Advantageously, strands or filaments in a layer are deposited at a distance from each other, thereby forming (large) pores between strands or filaments. Advantageously, strands or filaments are deposited in such a way that the filaments or strands of adjacent layers intersect each other, or are at least partially arranged to overlap each other. Therefore, the long filaments or the stock of adjacent layers come into contact, thereby causing the connection between adjacent / continuous layers. Advantageously, the porous green compact is to be constructed by depositing the building material as long filaments or stock to build a three-dimensional structure (e.g., via (micro) extrusion). Immediately after deposition, the organic binder in the long filaments or stock is advantageously (at least partially) dissolved in a solvent. In a subsequent step, the solvent is removed via phase inversion, as will be further described below.
[0092] Advantageously, the filaments or strands have a diameter between 20 μm and 5 mm, preferably between 30 μm and 4 mm, more preferably between 50 μm and 3 mm, for example between 100 μm and 2 mm.
[0093] The (macro)porosity of the porous green body may vary depending on the final application or use of the porous (3D printed) structure. The porosity may be varied by adapting the 3D printing process parameters, which is known in the art how to do so. Advantageously, the pores between adjacent filaments or strands have an average size between 1 μm and 5 mm, preferably between 20 μm and 4 mm, more preferably between 50 μm and 3 mm, for example between 100 μm and 2 mm.
[0094] The porous green body and 3D porous adsorbent structure obtained by the method of the present disclosure can have a variety of geometric shapes. The green body is advantageously a monolith. It can be a monolith having a rectangular parallelepiped or cylindrical shape.
[0095] Advantageously, the (initial or original) inorganic porous adsorbent material, i.e. the inorganic porous adsorbent material as is, has a thickness of at least 20 m 2 / g, preferably at least 25m 2 / g, more preferably at least 50m 2 / g, such as at least 75m2 / g, or at least 100m 2 / g, wherein the BET surface area is advantageously determined from a nitrogen adsorption isotherm at 77K, or alternatively from an argon adsorption isotherm at 87K.
[0096] Advantageously, the inorganic porous adsorbent material is a particulate material, such as a powder. Advantageously, the inorganic porous adsorbent material particles have a particle size distribution having a diameter between 1 / 5 and 1 / 20 of the diameter of the filament or strand, preferably between 1 / 7 and 1 / 15 of the diameter of the filament, such as substantially 1 / 10. 50 value.
[0097] Non-limiting examples of metal oxides suitable as inorganic porous adsorbent materials include silicon dioxide, titanium dioxide, aluminum oxide and zirconium oxide. Non-limiting examples of carbon-based materials include activated carbon, carbon molecular sieves and carbon nanotubes (CNTs). Non-limiting examples of clays include natural clay minerals and synthetic clays, such as bentonite clay, attapulgite, fuller's earth, kaolin, synthetic laponite (laponite) and wollastonite. Non-limiting examples of molecular sieves include aluminosilicates and titanosilicates. MXene includes a few atomically thick layers of transition metal carbides, nitrides or carbonitrides. Preferred inorganic porous adsorbent materials include zeolites and metal organic frameworks. An example of a suitable zeolite is 13X.
[0098] Optionally, the inorganic porous adsorbent material may be functionalized. Functionalization may include silanization, phosphonic acid treatment, impregnation, or grafting functional groups on at least a portion of the surface of the inorganic porous adsorbent material. Advantageously, functionalization produces an inorganic porous adsorbent material with an increased ability to interact with the environment.
[0099] Advantageously, the method of the present disclosure allows obtaining a 3D porous adsorbent structure comprising a functionalized inorganic porous adsorbent material. An advantage of the method of the present invention is that, as explained above and below, the temperature to which the porous green body and the porous adsorbent structure are exposed is kept relatively low, preferably below 180° C. This allows maintaining the functionality of the functional groups, since these functional groups are usually temperature sensitive and tend to degrade when exposed to elevated temperatures.
[0100] The inorganic porous adsorbent material can be dried before adding it to the build material. This reduces the risk of initiating phase transformation during the construction of the 3D porous green body or even during storage of the adsorbent material before use (e.g. before adding it to the build material). This further allows for improved control of pore formation (amount, size).
[0101] Advantageously, the building material comprises at least 30% by weight, preferably between 30 and 70% by weight, such as between 40 and 60% by weight, more preferably between 45 and 55% by weight, such as between 45 and 50% by weight, of inorganic porous adsorbent material based on the total weight of the building material.
[0102] Advantageously, the building material comprises 30% or less by weight, preferably between 5% and 30% by weight, such as between 5% and 25% by weight, between 5% and 20% by weight, between 5% and 15% by weight, more preferably between 10% and 15% by weight, of organic binder material based on the total weight of the building material.
[0103] The build material may further include one or more additives. The additives may be selected to act as plasticizers, dispersants, and / or pore formers (but are not limited thereto). Examples of such additives are calcium carbonate, 1,4-dioxane, and diethylene glycol dimethyl ether.
[0104] Advantageously, the building material comprises at least 35% by weight, preferably more than 40% by weight, such as more than 45% by weight, more preferably more than 50% by weight, most preferably more than 55% by weight of solid content based on the total weight of the building material. The solid content includes an inorganic porous adsorbent material, an organic binder material and further optional compounds such as a plasticizer and a dispersant.
[0105] The solvent advantageously comprises a polar aprotic solvent. Advantageously, at least a portion of the organic binder material is dissolved in the solvent. The solvent can be a non-volatile liquid, a volatile liquid or a mixture thereof. Preferred solvents include NMP (non-volatile solvent) and acetone (volatile solvent).
[0106] Advantageously, the build material comprises at least 5% by weight, preferably at least 10% by weight, for example at least 20% by weight, at least 30% by weight, more preferably at least 35% by weight of solvent, based on the total weight of the build material.
[0107] Advantageously, the build material comprises between 5 and 65% by weight, preferably between 20 and 55% by weight, such as between 30 and 50% by weight, more preferably between 35 and 45% by weight, of solvent based on the total weight of the build material.
[0108] Advantageously, the amount of solvent is selected based on the type and amount of the adsorbent material and the binder material to obtain a build material having a viscosity required by the method or technique for building the 3D porous green body. Depending on the technique or method used to build the 3D porous green body, the optimal viscosity varies. For example, when applying an extrusion-based 3D printing technique, the viscosity of the solvent is about 0.01 s-1 The shear rate and temperature of 25°C, the building material advantageously has a shear rate of 10 Pa.s and a shear rate of 10 Pa.s and a shear rate of 25°C. 6 mPa.s, preferably between 10 2 mPa.s vs 10 6 The viscosity when printing is between mPa.s (so-called printable (shear-thinning) viscosity).
[0109] The building material can be prepared according to various routes, and any of them can be used in the methods of the present disclosure. In some examples, the inorganic porous adsorbent material and the organic binder material are mixed together in a solvent to obtain the building material.
[0110] Alternatively, two or more separate solutions are prepared, each solution comprising at least one different component of the build material. These separate solutions are then mixed to obtain the build material. For example, a first solution and a second solution are prepared. The first solution can be prepared by mixing an inorganic porous adsorbent material in (a portion of) a solvent, preferably without adding an organic binder material. The second solution can be prepared by mixing an organic binder material in (a portion of) a solvent, preferably without adding an inorganic porous adsorbent material, thereby at least partially dissolving the organic binder material in the solvent. The first solution and the second solution are then mixed to obtain a modulator.
[0111] Advantageously, the building material having the composition as described above provides sufficient mechanical strength for the porous green body during the deposition of the filaments of the building material in a plurality of stacked layers to obtain the porous green body. The inventors believe that this mechanical strength is attributed to the organic binder material. Therefore, no stabilization is required during the construction of the porous green body, such as spraying water or building in a humid environment to start (i.e., induce) phase transformation during the construction. The inventors have found that even with a small amount, for example as low as 5% and up to 10% by weight of the organic binder material based on the weight of the building material, sufficient mechanical strength is obtained during the construction. Such a small amount also has the following advantages: the accessibility of the inorganic adsorbent material in the obtained 3D porous adsorbent structure is high, and the (micro) pores of the inorganic adsorbent material are mostly maintained. Further, the obtained 3D porous structure also has sufficient mechanical strength for the intended use.
[0112] Optionally, the 3D porous green body may also be exposed to a non-solvent during the construction of the 3D porous green body. This may be achieved by atomizing or spraying water or another non-solvent onto the specific layer of the green body once the filaments forming one or more layers have been deposited. Alternatively, the construction step may be performed in a humid atmosphere, i.e., an atmosphere having a relative humidity of at least 50% RH, preferably at least 75% RH, more preferably at least 80% RH, or at least 90% RH.
[0113] In the second step of the method of the present disclosure, the porous green body is subjected to a phase inversion. During the phase inversion, the porous green body is exposed to a non-solvent for the organic binder material. Advantageously, the solvent contained in the porous green body is miscible or soluble in the non-solvent.
[0114] After exposure to the non-solvent, the binder solution is separated into a phase rich in binder (polymer) and a phase poor in binder (polymer). After further separation, the solubility of the binder (polymer) decreases and a solid phase with a specific morphology will be formed. This leads to the solidification of the porous green body.
[0115] Advantageously, the structure of the porous green compact does not significantly change during the phase inversion. In other words, the structure of a plurality of stacked layers (the stacked layers are constructed by filaments, wherein at least some of the filaments in at least one of the plurality of layers are spaced apart from each other) is substantially maintained during the phase inversion. In other words, the solidified porous green compact advantageously includes filaments in a plurality of stacked layers, wherein at least some of the filaments in at least one of the plurality of layers are spaced apart from each other.
[0116] Phase inversion also results in the formation of pores, particularly micropores, in the solidified porous green compact. According to the IUPAC definition, micropores are pores with a diameter less than 2nm. Porosity depends largely on the type of solvent / non-solvent system that affects the kinetics of the delamination process. For example, the instantaneous delamination that occurs very quickly after immersion typically produces a relatively porous matrix. For example, delayed delamination typically results in reduced porosity and more spongy pores. In other words, by selecting solvent and non-solvent, porosity can be controlled.
[0117] Advantageously, the non-solvent comprises or is substantially composed of a polar protic solvent. Advantageously, the non-solvent is a liquid or a vapor. Non-limiting examples of liquid non-solvents include water, alcohols (e.g., methanol, ethanol, n-propanol or isopropanol), acids (e.g., acetic acid) or a combination of two or more thereof. Preferably, the non-solvent comprises or is substantially composed of water (e.g., demineralized water).
[0118] Phase inversion can be induced by techniques known in the art. Non-limiting examples include immersing the 3D porous green body in a non-solvent, atomizing, spraying or nebulizing the non-solvent onto the three-dimensional porous green body, or exposing the 3D porous green body to one or more of an atmosphere comprising or consisting essentially of a non-solvent.
[0119] In the third step of the method of the present disclosure, the solidified porous green body is dried. Drying allows the removal of the remaining solvent and / or non-solvent from the solidified porous green body, thereby obtaining a three-dimensional porous adsorbent structure.
[0120] Advantageously, the structure of the solidified porous green body is not significantly changed during drying. In other words, the structure of the plurality of stacked layers (the stacked layers are constructed of filaments, wherein at least some of the filaments in at least one of the plurality of layers are spaced apart from each other) is substantially maintained during drying. In other words, the three-dimensional porous adsorbent structure advantageously comprises filaments in the plurality of stacked layers, wherein at least some of the filaments in at least one of the plurality of layers are spaced apart from each other.
[0121] Drying is advantageously carried out at a temperature below the melting temperature of the organic binder material, or below the glass transition temperature when the organic binder material comprises a polymer. By drying at such temperatures, damage to and / or any removal of the organic binder material can be avoided. Thus, and advantageously, the three-dimensional porous adsorbent structure obtained after drying comprises at least a portion of the organic binder material. Further, by avoiding damage to or removal of at least a portion of the organic binder material, the mechanical strength of the 3D porous adsorbent structure can be maintained.
[0122] Further, since the organic binder material does not melt, it does not flow into the pores of the 3D porous adsorbent structure and / or the pores of the inorganic adsorbent material itself, which allows the accessibility and porosity of the inorganic porous adsorbent material to be maintained.
[0123] The drying temperature is advantageously selected based on the organic binder material. Advantageously, drying is at a temperature lower than the highest continuous use temperature of the organic binder material, such as at least 5°C, at least 10°C, at least 20°C or at least 30°C lower than the highest continuous use temperature, for example, at a temperature between 5°C and 50°C lower than the highest continuous use temperature. The highest continuous use temperature is as described above. Advantageously, drying is between 20°C and 180°C, preferably between 20°C and 150°C, such as between 20°C and 130°C, such as between 20°C and 100°C, at a temperature between 20°C and 75°C, such as at room temperature. For example, polysulfone has a maximum continuous use temperature of 180°C, and drying is advantageously carried out at a temperature between 20°C and 150°C. For example, polyvinylidene fluoride has a maximum continuous use temperature of 150°C and drying is advantageously carried out at a temperature between 20°C and 130°C.
[0124] Advantageously, the three-dimensional porous green body and the three-dimensional porous adsorbent structure are not exposed to a temperature higher than the maximum continuous use temperature of the organic binder material. Advantageously, the three-dimensional porous green body and the three-dimensional porous adsorbent structure are not exposed to a temperature higher than 180°C. Therefore, and advantageously, at least a portion of the organic binder material remains in the three-dimensional porous adsorbent structure. Advantageously, the three-dimensional porous adsorbent structure is not subjected to any heat treatment higher than the maximum continuous use temperature of the organic binder material. Advantageously, the three-dimensional porous adsorbent structure is not subjected to any heat treatment higher than 180°C. The heat treatment may be any of a calcination and a sintering operation.
[0125] A second aspect of the present invention relates to a three-dimensional porous adsorbent structure comprising at least 50% by weight of an inorganic porous adsorbent material and 50% by weight or less of an organic binder material, based on the total weight of the three-dimensional porous adsorbent structure, characterized in that the three-dimensional porous adsorbent structure has an adsorbent accessibility of at least 40%, wherein the adsorbent accessibility is calculated according to formula (I):
[0126]
[0127] in
[0128] S BET,结构 is the BET surface area of the three-dimensional porous adsorbent structure,
[0129] S BET,吸附剂 is the BET surface area of the initial inorganic porous adsorbent material,
[0130] X is the weight percentage of the inorganic porous adsorbent material based on the total weight of the three-dimensional porous adsorbent structure,
[0131] And wherein the BET surface area of the initial inorganic porous adsorbent material and the three-dimensional porous adsorbent structure is determined from an argon adsorption isotherm at 87K.
[0132] The three-dimensional porous adsorbent structure of the present invention comprises an inorganic porous adsorbent material and an organic binder material. Advantageously, the inorganic porous adsorbent material and the organic binder material are as described above. Therefore, the 3D porous adsorbent structure can be considered as a hybrid organic / inorganic structure or a composite material. When the organic binder material comprises a polymer as described above and the inorganic adsorbent material comprises a zeolite, the structure can be considered as a hybrid polymer / zeolite structure or a composite material. Advantageously, the three-dimensional porous adsorbent structure is obtained by the method of the present invention.
[0133] The 3D porous adsorbent structure advantageously comprises at least 50% by weight, preferably between 60 and 98% by weight, more preferably between 70 and 98% by weight, for example between 75 and 95% by weight, most preferably between 80 and 95% by weight, of inorganic porous adsorbent material based on the total weight of the three-dimensional porous adsorbent structure.
[0134] The 3D porous adsorbent structure advantageously comprises at least 50 vol.%, preferably between 60 and 98 vol.%, more preferably between 70 and 98 vol.%, for example between 70 and 95 vol.%, most preferably between 75 and 95 vol.% inorganic porous adsorbent material.
[0135] The 3D porous adsorbent structure advantageously comprises 50% or less by weight, preferably between 2% and 40% by weight, more preferably between 2% and 30% by weight, for example between 5% and 25% by weight, most preferably between 5% and 20% by weight, of organic binder material based on the total weight of the three-dimensional porous adsorbent structure.
[0136] The 3D porous adsorbent structure advantageously comprises 50 vol.% or less, preferably between 2 vol.% and 40 vol.%, more preferably between 2 vol.% and 30 vol.%, for example between 5 vol.% and 30 vol.%, most preferably between 5 vol.% and 25 vol.% of organic binder material.
[0137] Advantageously, the three-dimensional adsorbent structure, and in particular the three-dimensional adsorbent structure obtained by the process of the present invention, has an adsorbent accessibility of at least 40%, such as at least 50%, at least 60% or at least 70%. The adsorbent accessibility is advantageously calculated according to formula (I):
[0138]
[0139] in
[0140] S BET,结构 is the BET surface area of the three-dimensional porous adsorbent structure,
[0141] S BET,吸附剂 is the BET surface area of the initial (or original) inorganic porous adsorbent material, wherein the initial inorganic porous adsorbent material is as defined above, and
[0142] X is the weight percent of the inorganic porous adsorbent material based on the total weight of the three-dimensional porous adsorbent structure.
[0143] Advantageously and preferably, the BET surface area of the initial (original) inorganic porous adsorbent material and the three-dimensional porous adsorbent structure is determined by an argon adsorption isotherm at 87 K. Alternatively, the BET surface area of the initial inorganic porous adsorbent material and the three-dimensional porous adsorbent structure may be determined by a nitrogen adsorption isotherm at 77 K. According to IUPAC, it is considered that the determination of the BET surface area by an argon adsorption isotherm at 87 K is more accurate than that by a nitrogen adsorption isotherm at 77 K, in particular with regard to the detection and measurement of micropores. According to the present invention, the BET surface area represents a specific surface area as calculated by the Brunauer-Emmett-Teller (BET) method.
[0144] In formula (i), “X*S BET,吸附剂 ” is the so-called theoretical maximum, which is the BET surface area of the initial inorganic porous adsorbent material multiplied by its weight percentage in the 3D porous adsorbent structure. Therefore, the closer the adsorbent accessibility is to 100%, the closer the BET surface area of the adsorbent structure is to the theoretical maximum, and the lower the impact of the organic binder on the surface area (such as by filling the pores or forming a layer on the adsorbent material). Therefore, a high adsorbent accessibility of at least 40% can be considered a measure of a high-performance adsorbent structure.
[0145] Advantageously, the three-dimensional porous adsorbent structure of the present invention, and in particular the three-dimensional porous adsorbent structure obtained by the method of the present invention, has a micropore volume of at least 30% of the micropore volume of the initial (or original) inorganic porous adsorbent material. As used herein, the micropore volume advantageously represents the total volume of the micropores in the structure. Advantageously, and preferably, the micropore volume of the initial inorganic porous adsorbent material and the three-dimensional porous adsorbent structure is determined by the t-plot method according to the argon adsorption isotherm at 87K. Alternatively, the micropore volume of the initial inorganic porous adsorbent material and the three-dimensional porous adsorbent structure can be determined by the t-plot method according to the nitrogen adsorption isotherm at 77K. Because argon does not have a quadrupole moment and is less reactive than diatomic nitrogen molecules, IUPAC actually recommends argon measurements at 87K for surface area and pore size distribution determination compared to nitrogen measurements at 77K.
[0146] Examples of suitable applications of the three-dimensional porous adsorbent structure according to aspects of the present invention are:
[0147] - Purification of gaseous or liquid streams by adsorption of one or more compounds;
[0148] - separation of certain compounds or components from gas or liquid streams by adsorption of such compounds or components;
[0149] - Selective adsorption of metal ions from process (liquid) streams;
[0150] - Biocatalysis to achieve certain reactions in liquid streams at relatively low temperatures, for example by immobilizing enzymes or microorganisms by adsorbing such enzymes or microorganisms on adsorbent structures.
[0151] Advantageously, the three-dimensional porous adsorbent structure of the present invention, and in particular the three-dimensional porous adsorbent structure obtained by the method of the present invention, is particularly suitable for adsorbing CO from a gaseous or liquid stream. 2 Advantageously, they are also particularly suitable for adsorbing water from gaseous or liquid streams.
[0152] Advantageously, the rate at which a compound is adsorbed is represented by the overall mass transfer coefficient k of the adsorbed compound during its adsorption and / or desorption. Advantageously, the overall mass transfer coefficient is calculated using the linear driving force model (LDF) described by Glueckauf and Coates.
[0153] Example
[0154] Three building materials were prepared, each containing zeolite 13X (Sylosiv A10H, Grace) as the inorganic porous adsorbent material. Three different polymers were used as organic binder materials: polysulfone (PSF, Amoco), polyvinylidene fluoride (PVDF Kynarflex 2801, Arkema), and polyamide-imide (Torlon 4000TF, Solvay).
[0155] A highly concentrated polymer solution containing 22.9% by weight of PSF, 22.6% by weight of PVDF and 22.2% by weight of Torlon, respectively, was prepared by dissolving the polymer in N-methyl-2-pyrrolidone (NMP, Brenntag) by stirring the solution for 15 min using an IKA 400 overhead stirrer. The resulting polymer solution was then kept on a roller table overnight to ensure complete dissolution of the polymer.
[0156] Before adding zeolite 13X to the polymer solution, the zeolite was dried overnight at 473K to eliminate the adsorbed water content. After drying, a certain mass of the heated zeolite powder was mixed with each of the three polymer solutions to achieve a build material containing a zeolite / polymer ratio of 80w% / 20w% each. This produced a build material with a total solid content of 59.7%, 59.4% and 58.8% for the zeolite / PSF, zeolite / PVDF and zeolite / Torlon build materials, respectively.
[0157] A reference build material comprising a typical ceramic binder combination was also prepared. Zeolite 13X as an inorganic porous adsorbent material was mixed with a compound comprising 50% by weight of bentonite (VWR) and 50% by weight of a colloidal silica solution (Ludox AS-40, Grace Company), based on the total weight of the compound. A build material with a zeolite / binder weight ratio of 80w% / 20w% was obtained. Next, methylcellulose (Merck) was added as a rheology modifier to achieve the desired viscosity. This produced a reference build material with a solids content of 57%.
[0158] The building material is loaded into a syringe (individually) and extruded through a thin nozzle by using a mechanically driven piston installed on a computer numerical control (CNC) machine. In this way, a constant volume flow rate is ensured and porous green compacts are built layer by layer. Two nozzle sizes (including 600 μm and 1200 μm) are used to construct a square monolithic structure of 3 cm height and 3 cm diameter. The distance between adjacent filaments is kept equal to the filament diameter, while each continuous layer is rotated 90 °, thereby running through the porous green compact to produce a straight channel of macropore size.
[0159] After printing, the porous green body obtained from the building material according to the present invention was immersed in demineralized (DI) water as a non-solvent for 16 h to induce the exchange of NMP (solvent) with DI water (non-solvent) and the precipitation (solidification) of the polymer. Afterwards, the solidified porous green body was dried at room temperature to remove any remaining or residual water, which produced a 3D porous adsorbent structure.
[0160] The green bodies obtained from the reference build materials were not subjected to a phase inversion step, but were dried at room temperature for 2 days and then calcined at 823 K to thermally decompose the organic binder material.
[0161] Characterization of 3D porous adsorbent structures (monoliths)
[0162] Before characterizing the 3D porous adsorbent structures obtained according to the present invention, they were activated (degassed) by heating them under vacuum overnight. The structures containing PSF and polyamide-imide were degassed at 423 K. The structures containing PVDF were degassed at 383 K due to the thermal instability of PVDF at 423 K.
[0163] The porosity of the 3D porous adsorbent structure according to the present invention obtained with a nozzle size of 600 μm was evaluated by comparing the specific surface area, total pore volume and pore size distribution with the corresponding values of the initial zeolite 13X (i.e. the zeolite 13X before it was added to the building material). The results are presented in Table 1.
[0164] To this end, the argon isotherm of each sample was measured on a Quantachrome Autosorb AS-1 in a degassing configuration at 87 K, and the nitrogen isotherm of each sample was measured on a Quantachrome Autosorb-iQ-MP (volumetric) in a degassing configuration at liquid nitrogen temperature (77 K).
[0165] The specific surface area (so-called BET surface area, S in Table 1) was calculated by the Brunauer-Emmett-Teller (BET) method. BET ). Argon has no quadrupole moment and is less reactive than diatomic nitrogen molecules, and therefore IUPAC actually recommends argon measurements at 87 K over nitrogen measurements at 77 K for surface area and pore size distribution determinations, the results of both of which are mentioned in Table 1.
[0166] Looking at the argon isotherm and the results of degassing at 423 K, the initial zeolite 13X has a 787 m 2 / g, while the zeolite / PSF adsorbent structure has a BET surface area of 572 m 2 / g, and the zeolite / polyamide-imide (zeolite / Torlon in Table 1) has a BET surface area of 427 m 2 / g, which are 72.7% and 54.3% of the BET surface area of the initial zeolite 13X, respectively. Looking at the argon isotherm and the results of degassing at 383K, the initial zeolite 13X has a BET surface area of 586 m 2 / g, while the zeolite / PVDF adsorbent structure has a BET surface area of 432 m 2 / g, which is 73.7% of the BET surface area of the initial zeolite 13X.
[0167] Figure 1Argon adsorption isotherms for the initial zeolite degassed at 423K 1 and 383K 2, argon adsorption isotherms at 80% (theoretical maximum) of the value for the initial zeolite degassed at 423K 3 and 383K 4, and adsorption isotherms for zeolite / PSF adsorbent structure 5, zeolite / PVDF adsorbent structure 6, and zeolite / Torlon adsorbent structure 7 are shown. The values of the BET surface area correspond well to the expected values for structures containing PSF and PVDF. In fact, because the zeolite can be considered to be 'diluted' to 80% due to the presence of the organic binder material, the "theoretical maximum" can be considered to be 80% of the initial zeolite 13X value. This indicates that PSF and PVDF have sufficient porosity to allow excellent access to the zeolite. However, for the adsorbent structure containing polyamide-imide (Torlon), a significant reduction in specific surface area is observed. Further, the high amount of argon adsorption at the lower pressure range indicates the presence of microporosity (which is a characteristic of the microporous nature of the zeolite powder).
[0168] The total pore volume of the 3D porous adsorbent structure (V in Table 1) 总 ) was calculated by the Barrett-Joyner-Halenda (BJH) method using the argon adsorption isotherm at 87 K.
[0169] The volume of micropores (V in Table 1 mic ) was calculated by the t-plot method using the argon adsorption isotherm at 87 K. The initial zeolite 13X had a 0.291 cm 3 / g of micropore volume, while the zeolite / PSF adsorbent structure has a micropore volume of 0.207 cm 3 / g, and the zeolite / polyamide-imide (zeolite / Torlon in Table 1) has a micropore volume of 0.154 cm 3 The micropore volume of the initial zeolite 13X after degassing at 383 K is 0.286 cm 3 / g of micropore volume, while the zeolite / PVDF adsorbent structure has a micropore volume of 0.214 cm 3 / g of micropore volume, which is 74.8% of the micropore volume of the initial zeolite 13X.
[0170] The values of the micropore volume correspond well to the expected values for a structure comprising PSF and PVDF, indicating that PSF and PVDF do not appear to fill or block the (micro)pores of zeolite 13X to a significant extent. Indeed, since the zeolite can be considered to be 'diluted' to 80% due to the presence of the organic binder material, the "theoretical maximum" can be considered to be 80% of the initial zeolite 13X value. However, for the adsorbent structure comprising polyamide-imide (Torlon), a significant reduction in the micropore volume was observed.
[0171] Table 1 - Surface area, pore volume and zeolite accessibility of zeolite 13X powder and three 3D porous adsorbent structures of the present invention (600 μm nozzle)
[0172]
[0173] The pore size distribution was determined on the argon adsorption isotherm at 87 K by using nonlocal density functional theory (NLDFT). Figure 2 Results are shown for the initial zeolite degassed at 423K 10 and 383K 11, as well as zeolite / PSF adsorbent structure 12, zeolite / PVDF adsorbent structure 13, and zeolite / Torlon adsorbent structure 14. Comparing the pore size distribution of the zeolite powder to the porous adsorbent structure, no significant differences were observed for the zeolite / PVDF adsorbent structure, and a small shift to lower pore sizes was observed for the zeolite / PSF adsorbent structure. This indicates that most of the zeolite structure is preserved.
[0174] This was further confirmed by scanning electron microscopy (SEM) images of the surface morphology of the two adsorbent structures, which were acquired using a FEGFEI Nova NanoSEM 450 at an accelerating voltage of 5 kV. Figure 3A shows the surface of a single filament of a zeolite / PSF adsorbent structure, and Figure 3B A cross section thereof is shown. Figure 4A shows the surface of a single filament of a zeolite / PVDF adsorbent structure, and Figure 4B A cross section thereof is shown. At the surface there is a clear outer polymer layer, which is obtained by phase inversion. The solvent / non-solvent exchange appears to have created a porous network on the outside of the fiber, ensuring easy accessibility of the zeolite particles and preventing them from diffusing out of the polymer composite.
[0175] In contrast to PVDF and PSF, the addition of Torlon polymer to the zeolite powder significantly reduces the total volume adsorbed to a greater extent than the theoretical maximum. Furthermore, a hysteresis curve is formed, which may be the first indication of the classic pore / ink bottle type blockage or diffusion of the polyamide-imide polymer into the zeolite pores. This is also observed as a shift in the derived pore size distribution, where the peak intensity at 0.75 nm pore width increases significantly. This is also confirmed by scanning electron microscopy (SEM) images of the surface morphology. Figure 5A The surface of a single filament of a zeolite / Torlon adsorbent structure is shown from which it appears that several sections of the polymer have fused together, thereby blocking access to the zeolite. Figure 5B A cross section of a single filament of a zeolite / Torlon adsorbent structure is shown.
[0176] When the zeolite accessibility is calculated according to formula (I) as presented above, a significant decrease is observed for the zeolite / Torlon adsorbent structure, likely and as explained above, caused by pore blocking by the polymer. However, in the zeolite / PSF and zeolite / PVDF adsorbent structures, more than 90% of the zeolite material remains accessible.
[0177] The mesoporosity and macroporosity of the three porous adsorbent structures of the present invention were measured by mercury intrusion porosimetry on a Thermo Electron Corporation Pascal 140-240 series. Figure 6 The (medium and macro) pore size distributions of the zeolite / PVDF adsorbent structure 20, the zeolite / PSF adsorbent structure 21, and the zeolite / Torlon adsorbent structure 22 are shown. Figure 7 The cumulative pore volume of the zeolite / PVDF adsorbent structure 30, the zeolite / PSF adsorbent structure 31, and the zeolite / Torlon adsorbent structure 32 are shown. A high degree of mesoporosity and macroporosity is observed. The polymer used as the organic binder material has a great influence on the pore size distribution and the total porosity of the structure. The highest pore volume is observed in the PVDF composite, which exhibits a major pore width of about 0.35 μm and a pore size of 528 μm. 3 The PSF and Torlon composites showed significantly lower pore volumes, with cumulative volumes of 335 m / g for the PSF and Torlon composites, respectively. 3 / g and 345mm 3While the PSF composite also showed a unimodal pore distribution with a major pore width of about 0.25 μm, a trimodal pore distribution with major pore diameters at 0.03 μm, 0.09 μm and 0.20 μm was observed for the Torlon composite.
[0178] Adsorption performance
[0179] The CO degassing sorbent structure obtained with a 600 μm nozzle was evaluated based on isotherm measurements performed at 273 K on a Chemstar TPx chemisorption analyzer (Quantachrome Instruments). 2 Adsorption performance. Helium as carrier gas was used at a flow rate of 200 mL / min. The same measurements were also performed on the initial zeolite 13X, which was degassed at the same temperature as the adsorbent structure to which it was compared. Further, the ceramic zeolite / clay reference sample was also measured after degassing at 383 K to evaluate the effect of the polymer binder compared to the clay binder. The static CO 2 The adsorption capacities are presented in Table 2.
[0180] Based on the static adsorption capacity of the zeolite and adsorbent structure, the relative capacity was calculated as the CO 2 The adsorption capacity is divided by 80% of the value of pure initial zeolite, since the adsorbent structure contains 80% zeolite by weight. The closer this value is to 100%, the less the binder material reduces CO 2 It is clear that all adsorbent structures obtain high values (above 90%), while the zeolite / Torlon adsorbent structure has a relative capacity above 100%. The latter may indicate that the Torlon polymer itself also adsorbs CO to some extent. 2 .
[0181] Water isotherm measurements were performed on a degassed adsorbent structure under isothermal conditions at 298 K using an IGAsorp standard dynamic vapor sorption (DVS) analyzer and both kinetic information and equilibrium absorption were determined simultaneously. The carrier gas used throughout the measurements was technical grade nitrogen (Air products) at a flow rate of 250 mL / min. Distilled water was used in the IGAsorp reservoir to humidify the gas when necessary. The static water adsorption capacities as measured are presented in Table 2.
[0182] Comparison of total H in polymer composites and pure zeolite powder 2O uptake, the adsorption capacity is very close to the theoretical maximum. Relative weight changes of 93.3%, 86.8% and 103.1% were calculated for the porous adsorbent structures based on PSF, PVDF and Torlon, respectively, which are defined as the water adsorption capacity of the adsorbent (or its weight gain) divided by 80% of the value of the pure initial zeolite. Such high values indicate the unchanged accessibility of the zeolite pores. The relative weight change of 122.6% was calculated for the zeolite / clay adsorbent structure. This extremely high value can be explained by the presence of plate-like clay particles, which create slit-shaped pores.
[0183] Table 2 - CO of zeolite powder, reference 3D porous adsorbent structure and three 3D porous adsorbent structures of the present invention 2 and H 2 O adsorption capacity
[0184]
[0185] 1 CO measured at 1 bar absolute pressure 2 capacity
[0186] 2 Equal to the ratio between the sample volume / weight change and 80% of the reference zeolite
[0187] 3 Weight change measured at 90% relative humidity
[0188] Figure 8 CO as a function of pressure is shown for an initial zeolite 40 degassed at 423 K, a theoretical maximum 41 of 80% of the value for the initial zeolite, and a zeolite / clay adsorbent structure 42 with a filament fineness of 1200 μm and a zeolite / clay adsorbent structure 43 with a filament fineness of 600 μm (also degassed at 423 K). 2 Adsorption capacity. It was observed that in the lower pressure range, CO 2 The rapid increase in adsorption indicates the microporous nature of zeolite 13X. Further, the total adsorption capacity is very close to the theoretical maximum, regardless of filament size. This indicates that the presence of clay binder has no effect on the adsorption properties of the zeolite.
[0189] Fig. 9 CO as a function of pressure is shown for an initial zeolite 40 degassed at 423 K, a theoretical maximum 41 of 80% of the value for the initial zeolite, and a zeolite / PSF adsorbent structure 52 with a filament size of 1200 μm and a zeolite / PSF adsorbent structure 53 with a filament size of 600 μm (also degassed at 423 K). 2 Adsorption capacity. It was observed that in the lower pressure range, CO 2The rapid increase in adsorption indicates the microporous nature of zeolite 13X. Further, the total adsorption capacity is very close to the theoretical maximum, regardless of filament size. This indicates that the presence of the PSF binder has no significant effect on the adsorption properties of the zeolite.
[0190] Fig.10 CO as a function of pressure is shown for an initial zeolite 60 degassed at 383 K, a theoretical maximum 61 of 80% of the value for the initial zeolite, and a zeolite / PVDF adsorbent structure 62 with a filament fineness of 1200 μm and a zeolite / PVDF adsorbent structure 63 with a filament fineness of 600 μm (also degassed at 423 K). 2 Adsorption capacity. It was observed that in the lower pressure range, CO 2 The rapid increase in adsorption indicates the microporous nature of zeolite 13X. Further, the total adsorption capacity is very close to the theoretical maximum, regardless of filament size. This indicates that the presence of PVDF binder has no significant effect on the adsorption properties of the zeolite.
[0191] Fig.11 CO as a function of pressure is shown for an initial zeolite 40 degassed at 423 K, a theoretical maximum 41 of 80% of the value for the initial zeolite, and a zeolite / Torlon adsorbent structure 72 with a filament fineness of 1200 μm and a zeolite / Torlon adsorbent structure 73 with a filament fineness of 600 μm (also degassed at 383 K). 2 Adsorption capacity. Inconsistent adsorption capacity depending on filament size was noted. CO was observed in the case of 1200 μm filament size. 2 The absorption was significantly reduced, which is consistent with the 2 The results are consistent with the reduced total pore volume observed in the Ar porosity measurements. The adsorbent structure based on 600 μm thick filaments indicated an uptake slightly exceeding the theoretical maximum compared to 1200 μm thick filaments. This difference in adsorption capacity may indicate a different internal structure when comparing the two filament sizes and an accumulation of polymer in the inner core during the phase inversion process in the case of 1200 μm filaments. In addition, a possible explanation for the high adsorption capacity of 600 μm filaments may be the CO 2 The combination of interaction with the Torlon polymer and additional pore volume in the ultra-micropore range that cannot be detected by argon measurements but can be detected by CO 2 Molecules touched.
[0192] Fig.12The water adsorption capacity as a function of pressure for an initial zeolite 80 degassed at 423 K, a theoretical maximum value 81 of 80% of the value for the initial zeolite, and a zeolite / clay adsorbent structure 82 with a filament fineness of 1200 μm and a zeolite / clay adsorbent structure 83 with a filament fineness of 600 μm (also degassed at 423 K) are shown. The isotherm shape of the zeolite / clay adsorbent structure shows an H3 type hysteresis, regardless of the filament fineness. This can be attributed to the plate-like structure of the bentonite clay particles and their expansion and contraction.
[0193] Fig.13 The water adsorption capacity as a function of pressure is shown for the initial zeolite 80 degassed at 423 K, the theoretical maximum 81 of 80% of the value for the initial zeolite, and the zeolite / PSF adsorbent structure 92 with a filament fineness of 1200 μm and the zeolite / PSF adsorbent structure 93 with a filament fineness of 600 μm (also degassed at 423 K). The water adsorption isotherms of the adsorbent structures show a Type I isotherm, regardless of the filament fineness. This is believed to be characteristic of the microporous nature of the zeolite powder.
[0194] Fig.14 The water adsorption capacity as a function of pressure for the initial zeolite 100 degassed at 383 K, the theoretical maximum 101 of 80% of the value for the initial zeolite, and the zeolite / PVDF adsorbent structure 102 with a filament fineness of 1200 μm and the zeolite / PVDF adsorbent structure 103 with a filament fineness of 600 μm (also degassed at 423 K) are shown. The water adsorption isotherms of the adsorbent structures show a Type I isotherm, regardless of the filament fineness. This is considered to be characteristic of the microporous nature of the zeolite powder.
[0195] Fig.15 The water adsorption capacity as a function of pressure for the initial zeolite 80 degassed at 423K, the theoretical maximum value 81 of 80% of the value of the initial zeolite, and the zeolite / Torlon adsorbent structure 112 with a filament fineness of 1200μm and the zeolite / Torlon adsorbent structure 113 with a filament fineness of 600μm (also degassed at 383K) are shown. The water adsorption isotherms of the adsorbent structures show a hysteresis curve similar to that observed in the argon adsorption isotherm measurements. It is believed that this is caused by a combination of pore blockage of the polymer and chemical interactions of water molecules with the amine functional groups of the polyamide-imide (causing delayed desorption). Further, significantly reduced water absorption was observed in the case of 1200μm filament fineness compared to 600μm filaments, which is consistent with the reduced total pore volume observed in the N2 and Ar porosity measurements.
[0196] Adsorption kinetics
[0197] The adsorption kinetics of an adsorbent structure is a measure of the adsorption and desorption rates of the adsorbent structure. Higher adsorption kinetics indicate faster adsorption and desorption, and therefore the ability to perform more adsorption / desorption cycles within a given time frame, leading to more industrially interesting adsorbent structures.
[0198] The adsorption rate is expressed as an overall mass transfer coefficient k calculated using the linear driving force model (LDF) described by Glueckauf and Coates. Table 3 shows the overall mass transfer coefficient of water adsorption rate calculated based on the water isotherms discussed above for reference zeolite / clay adsorbent structures, zeolite / PSF adsorbent structures, zeolite / PVDF adsorbent structures, and zeolite / Torlon adsorbent structures. All four adsorbent structures with filaments of 600 μm and 1200 μm were tested, and the four adsorbent structures were degassed at the temperatures described above.
[0199] Table 3 - Mass transfer coefficients during adsorption and desorption for a reference 3D porous adsorbent structure and three 3D porous adsorbent structures of the present invention
[0200]
[0201] Fig.16 Shown are water absorption curves for a humidity step from 5% RH to 10% RH as a function of time measured on a single filament having a filament diameter of 1200 μm for a zeolite / clay reference adsorbent structure 120, a zeolite / PSF adsorbent structure 121, a zeolite / PVDF adsorbent structure 122, and a zeolite / Torlon adsorbent structure 123.
[0202] Fig.17 Shown are water absorption curves for a humidity step from 5% RH to 10% RH as a function of time measured on a single filament having a filament diameter of 600 μm for a zeolite / clay reference adsorbent structure 130, a zeolite / PSF adsorbent structure 131, a zeolite / PVDF adsorbent structure 132, and a zeolite / Torlon adsorbent structure 133.
[0203] exist Fig.16 and Fig.17 The slope of the linear portion of the initial water adsorption gives an indication of the absorption rate. A steeper curve, i.e. a higher absorption rate, implies a reduction in the total time to reach saturation. Fig.16 and Fig.17 Comparison between shows that a significantly increased diffusion coefficient is observed for the adsorbent with 600 μm filament diameter, indicating that the limitation of mass diffusion is reduced by reducing the filament diameter.
[0204] Further, as is also clear from Table 3, the zeolite / PSF and zeolite / PVDF adsorbent structures show comparable adsorption coefficients to the zeolite / clay reference adsorbent structure. In contrast to PSF and PVDF, the addition of Torlon polymer appears to slightly reduce the kinetic constants. However, this is closely related to the reduced total pore volume and pore size distribution as described previously, which may therefore be the main reason for the reduced absorption rate.
[0205] CO 2 The breakthrough curve is obtained at 10% applied CO 2 Measured at partial pressure. 2 The breakthrough curve is obtained by measuring the CO at the end of the column filled with adsorbent material. 2 The concentration is obtained, where CO at a certain partial pressure 2 Through the column. It is known that CO 2 The slope of the breakthrough curve reflects the CO 2 Adsorption kinetics.
[0206] Fig.18 The 10% CO absorption at relative times up to 1250 seconds is shown for the zeolite / clay reference adsorbent structure 140, the zeolite / PSF adsorbent structure 141, the zeolite / PVDF adsorbent structure 142, and the zeolite / Torlon adsorbent structure 143. 2 CO under partial pressure 2 Penetration curve.
[0207] from Fig.18 It is clear from the results that the zeolite / PSF and zeolite / PVDF adsorbent structures show very similar adsorption coefficients compared to the zeolite / clay reference adsorbent structure. In contrast to PSF and PVDF, the addition of Torlon polymer appears to slightly reduce the adsorption coefficients at low CO 2 The kinetic constants at 200 μg / min partial pressures are believed to be closely related to the reduced total pore volume and pore size distribution of the zeolite / Torlon adsorbent structure as already described above. As a conclusion, the presence of PSF polymer and PVDF polymer used to develop the hybrid zeolite composite did not negatively affect the CO 2 and H 2 O uptake kinetics and shows a very comparable behavior to the frequently used reference clay binders.
Claims
1. A method for producing a three-dimensional porous adsorbent structure, the method comprising: constructing a three-dimensional porous green body from a building material comprising a solvent, an inorganic porous adsorbent material, and an organic binder material, wherein at least a portion of the organic binder material is dissolved in the solvent, wherein the building material is deposited as filaments in a plurality of stacked layers to obtain the three-dimensional porous green body, wherein at least some of the filaments within at least one of the plurality of layers are spaced apart from each other, inducing a phase inversion of the three-dimensional porous green body by exposing the three-dimensional porous green body to a non-solvent for the organic binder material, thereby obtaining a solidified three-dimensional porous green body, and The solidified three-dimensional porous green body is dried to obtain the three-dimensional porous adsorbent structure, characterized in that the building material comprises between 30% and 70% by weight of the inorganic porous adsorbent material and between 5% and 30% by weight of the organic binder material based on the total weight of the building material, characterized in that the three-dimensional porous adsorbent structure comprises at least a portion of the organic binder material, and characterized in that the three-dimensional porous adsorbent structure has an adsorbent accessibility of at least 40%, wherein the adsorbent accessibility is calculated according to formula (I): in S BET,结构 is the BET surface area of the three-dimensional porous adsorbent structure, S BET,吸附剂 is the BET surface area of the initial inorganic porous adsorbent material, X is the weight percentage of the inorganic porous adsorbent material based on the total weight of the three-dimensional porous adsorbent structure, And wherein the BET surface area of the initial inorganic porous adsorbent material and the three-dimensional porous adsorbent structure is determined from an argon adsorption isotherm at 87K.
2. The method according to claim 1, wherein: The organic binder material comprises a phase inversion polymer, wherein, in the build material, the phase inversion polymer is dissolved in the solvent, and wherein the phase inversion is induced by exposing the three-dimensional porous green body to a non-solvent for the phase inversion polymer.
3. A method according to any one of the preceding claims, wherein: Phase inversion is induced by immersing the three-dimensional porous green body in the non-solvent and / or by atomizing the non-solvent onto the three-dimensional porous green body.
4. A method according to any one of the preceding claims, wherein: The drying is carried out at a temperature between 20°C and the maximum continuous use temperature of the organic binder material, preferably between 20°C and 180°C, more preferably between 20°C and 150°C, the maximum continuous use temperature as defined by the Underwriters Laboratories (UL) Relative Thermal Index (RTI).
5. A method according to any one of the preceding claims, wherein: The three-dimensional porous green body and the three-dimensional porous adsorbent structure are not exposed to temperatures above the maximum continuous use temperature of the organic binder material, preferably 180° C., as defined by the Underwriters Laboratories (UL) Relative Thermal Index (RTI).
6. A method according to any one of the preceding claims, wherein: The three-dimensional porous adsorbent structure was not subjected to any of the calcination and sintering operations.
7. A method according to any one of the preceding claims, wherein: The inorganic porous adsorbent material comprises one or more of: a zeolite adsorbent material, a metal organic framework (MOF) adsorbent material, a metal oxide, a carbon-based material, a clay, a molecular sieve, or a few-atom-thick layer of a transition metal carbide, nitride or carbonitride.
8. The method according to claim 7, wherein: The inorganic porous adsorbent material further comprises a catalytically active material provided on a surface of the inorganic porous adsorbent material, wherein the catalytically active material comprises an enzyme and / or a microorganism.
9. A method according to any one of the preceding claims, wherein: The organic binder material includes one or more of the following: polysulfone, polyethersulfone, cellulose acetate, polyvinylidene fluoride, polyacrylonitrile, polyethylene-co-vinyl alcohol or polycarbonate.
10. A method according to any one of the preceding claims, wherein: The build material comprises between 5 and 65% by weight, preferably between 20 and 55% by weight, of the solvent, based on the total weight of the build material.
11. A method according to any one of the preceding claims, wherein: The solvent includes a polar aprotic solvent, preferably N-methyl-2-pyrrolidone (NMP), acetone, dimethyl-acetamide (DMAc), dimethylformamide (DMF), dimethyl sulfoxide (DMSO), tetrahydrofuran (THF) or a combination of two or more thereof.
12. A method according to any one of the preceding claims, wherein: The non-solvent includes a polar protic solvent, preferably water, an alcohol, an acid or a combination thereof.
13. A method according to any one of the preceding claims, wherein: The build material is a viscous paste, emulsion or solution.
14. A three-dimensional porous adsorbent structure obtainable by a method according to any one of the preceding claims, the three-dimensional porous adsorbent structure comprising filaments in a plurality of stacked layers, wherein at least some of the filaments in one of the plurality of layers are spaced apart from each other, the three-dimensional porous adsorbent structure comprising at least 50% by weight of an inorganic porous adsorbent material and 50% by weight or less of an organic binder material, based on the total weight of the three-dimensional porous adsorbent structure, characterized in that The three-dimensional porous adsorbent structure has an adsorbent accessibility of at least 40%, wherein the adsorbent accessibility is calculated according to formula (I) in S BET,结构 is the BET surface area of the three-dimensional porous adsorbent structure, S BET,吸附剂 is the BET surface area of the initial inorganic porous adsorbent material, X is the weight percentage of the inorganic porous adsorbent material based on the total weight of the three-dimensional porous adsorbent structure, And wherein the BET surface area of the initial inorganic porous adsorbent material and the three-dimensional porous adsorbent structure is determined from an argon adsorption isotherm at 87K.
15. The three-dimensional porous adsorbent structure according to claim 14, comprising between 70% and 98% by weight of the inorganic porous adsorbent material and between 2% and 30% by weight of the organic binder material.
16. The three-dimensional porous adsorbent structure according to claim 14 or 15, which has a micropore volume of at least 30% of the micropore volume of the initial inorganic porous adsorbent material, wherein the micropore volume is determined by a t-plot method based on argon adsorption isotherms at 87K of the initial inorganic porous adsorbent material and the three-dimensional porous adsorbent structure.
17. The three-dimensional porous adsorbent structure according to any one of claims 14 to 16, wherein: The organic binder material is selected from one or more of the following: polysulfone, polyethersulfone, cellulose acetate, polyvinylidene fluoride, polyacrylonitrile, polyethylene-co-vinyl alcohol and polycarbonate.
18. Use of the three-dimensional porous adsorbent structure according to any one of claims 14 to 17 for gas adsorption applications and / or liquid adsorption applications, in particular for adsorption of one or more of CO2, volatile organic compounds, sulfur oxides and nitrogen oxides.
19. The use according to claim 18, wherein The three-dimensional porous adsorbent structure is not exposed to temperatures above the maximum continuous use temperature of the organic binder material, preferably 180° C., as defined by the Underwriters Laboratories (UL) Relative Thermal Index (RTI).
Citation Information
Patent Citations
3D printed zeolite monoliths for co2 removal
US20220250029A1
Method for producing a three-dimensional macroporous filament construct based on phase inversion and construct thereby obtained
WO2009027525A2